Oil & War How the Deadly Struggle for Fuel in World War II Meant Victory or Defeat, reprint edition - Goralski, Robert (Marine Corps University Press (MCUP), 2021)
The world's economy runs on oil. People steal for it. Nations kill for it. To win a war, the victor must have enough oil to fuel their tanks, ships, and planes. One of the great untold stories of World War II is about the strategic decisions and combat for the control of enough oil so that the Axis powers could wage an aggressive war. Conversely, the Allied powers were determined to keep oil from the Axis. Oil & War, originally published in 1987, was the first book to explain this intricate dance of death from the view-points of both the Axis and Allied sides. Adolf Hitler began planning his grab for oil-producing lands in the 1930s; he also started building plants capable of producing synthetic fuels. The Japanese had their plans too. The Americans, English, and Australians had to counterpunch. They very nearly lost the war because they did not move quickly enough. The race was far closer than previously believed. Truth is stranger than fiction. Novels and wargames based on the strategies for oil have captured the public's attention. But here is the real story. This anecdotal narrative about the important role that oil played in World War II provides a view of the forces that controlled the greatest war in history-and a stunning analysis of the importance of oil in terms of world peace for years to come.